2010
DOI: 10.1007/s10532-010-9378-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of haloalkaliphilic sulfur-oxidizing microorganisms with potential application in the effluent treatment of the petroleum industry

Abstract: Haloalkaliphilic sulfur-oxidizing mixed cultures for the treatment of alkaline-saline effluents containing sulfide were characterized and evaluated. The mixed cultures (IMP-PB, IMP-XO and IMP-TL) were obtained from Mexican alkaline soils collected in Puebla (PB), Xochimilco (XO) and Tlahuac (TL), respectively. The Ribosomal Intergenic Spacer Analysis (RISA) revealed bacteria related to Thioalkalibacterium and Thioalkalivibrio in IMP-XO and IMP-PB mixed cultures. Halomonas strains were detected in IMP-XO and IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Various thiosulphate concentrations were tested. 5 mM and 10 mM was set as minimum concentration (Olguin-Lora et al, 2011), 40 mM as initial concentration and 100 mM as a maximum concentration (Makzum et al, 2016). The cultures media were set at pH 8.0 (optimum pH) and incubated at a temperature of 30 °C (optimum temperature) with 160 rpm agitation speed for 7 d. For bacterial growth, 1 mL samples were withdrawn every 24 h and optical density was measured by spectrophotometer at 660 nm.…”
Section: Effects Of Physicochemical Properties On Microbial Growth Anmentioning
confidence: 99%
“…Various thiosulphate concentrations were tested. 5 mM and 10 mM was set as minimum concentration (Olguin-Lora et al, 2011), 40 mM as initial concentration and 100 mM as a maximum concentration (Makzum et al, 2016). The cultures media were set at pH 8.0 (optimum pH) and incubated at a temperature of 30 °C (optimum temperature) with 160 rpm agitation speed for 7 d. For bacterial growth, 1 mL samples were withdrawn every 24 h and optical density was measured by spectrophotometer at 660 nm.…”
Section: Effects Of Physicochemical Properties On Microbial Growth Anmentioning
confidence: 99%
“…A naturally adapted consortium to salinity conditions could represent the best alternative to treat saline effluents containing sulfide, nitrate, and C‐compounds. Certainly, previous reports have documented the use of halophilic or halotolerant microorganisms for the removal of sulfide , C‐pollutants , and nitrate ; nevertheless, to our knowledge, the simultaneous removal of these pollutants by these type of microorganisms has never been reported. Therefore, the aim of this study was to evaluate the capacity of a marine consortium for the simultaneous removal of sulfide, nitrate, and p ‐cresol.…”
Section: Introductionmentioning
confidence: 94%
“…It has been reported that alkaliphilic sulfur oxidizing bacteria (ASB) can oxidize reduced sulfur compounds such as sulfides and Thioalkalibacter are used in H 2 S removal studies. 27 These chemolithoautotrophic microorganisms can also grow in saline environments.…”
Section: Bacterial Community Analysismentioning
confidence: 99%